A study on pregenomic RNA and factors in the pregnant and postpartum women with chronic HBV infection based on real world - Tang, Juan; Wu, Qiuchen; Zhang, Ziyue; Zhou, Guanlun; Ji, Ying; Wu, Yandan; Wang, Genju (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMost studies have focused on mother-to-child transmission and postpartum hepatitis flares. We aimed to evaluate the expression profile of pregenomic RNA (pgRNA) and its associated factors in patients with chronic HBV infection (CHB) during pregnancy and postpartum.MethodsA total of 134 pregnant and 100 postpartum CHB patients were enrolled, and serum pgRNA levels were quantified.ResultsSignificant differences in clinical characteristics were noted between pregnant and postpartum CHB patients, but there was no significant difference in pgRNA levels between the two groups. When HBV DNA and HBV antigen levels were low, the corresponding pgRNA detection rate decreased. pgRNA was positively correlated with DNA and HBV antigens in the pregnant and postpartum CHB patients. In the pregnant group, antiviral treatment was an independent risk factor for pgRNA levels. In the postpartum period, HBeAg levels and antiviral treatment were independent risk factors for pgRNA levels. Considering that patients receiving antiviral treatment often have a high DNA load or HBeAg positivity, the DNA level and HBeAg essentially affect pgRNA levels. ConclusionpgRNA levels differ between pregnant and postpartum patients, and this difference is of great significance for the diagnosis and management of these particular groups.